IP-10 (CXCL10) Can Trigger Emergence of Dormant Breast Cancer Cells in a Metastatic Liver Microenvironment - Clark, Amanda M.; Heusey, Haley L.; Griffith, Linda G.; Lauffenburger, Douglas. A.; Wells, Alan (Frontiers in Oncology, 2021)
Metastatic breast cancer remains a largely incurable and fatal disease with liver involvement bearing the worst prognosis. The danger is compounded by a subset of disseminated tumor cells that may lie dormant for years to decades before re-emerging as clinically detectable metastases. Pathophysiological signals can drive these tumor cells to emerge. Prior studies indicated CXCR3 ligands as being the predominant signals synergistically and significantly unregulated during inflammation in the gut-liver axis. Of the CXCR3 ligands, IP-10 (CXCL10) was the most abundant, correlated significantly with shortened survival of human breast cancer patients with metastatic disease and was highest in those with triple negative (TNBC) disease. Using a complex ex vivo all-human liver microphysiological (MPS) model of dormant-emergent metastatic progression, CXCR3 ligands were found to be elevated in actively growing populations of metastatic TNBC breast cancer cells whereas they remained similar to the tumor-free hepatic niche in those with dormant breast cancer cells. Subsequent stimulation of dormant breast cancer cells in the ex vivo metastatic liver MPS model with IP-10 triggered their emergence in a dose-dependent manner. Emergence was indicated to occur indirectly possibly via activation of the resident liver cells in the surrounding metastatic microenvironment, as stimulation of breast cancer cells with exogenous IP-10 did not significantly change their migratory, invasive or proliferative behavior. The findings reveal that IP-10 is capable of triggering the emergence of dormant breast cancer cells within the liver metastatic niche and identifies the IP-10/CXCR3 as a candidate targetable pathway for rational approaches aimed at maintaining dormancy.